Effect of dorzolamide and timolol on ocular blood flow in patients with primary open angle glaucoma and ocular hypertension. Issue 10 (16th September 2005) - Fuchsjäger-Mayrl, G; Wally, B; Rainer, G; Buehl, W; Aggermann, T; Kolodjaschna, J; Weigert, G; Polska, E; Eichler, H-G; Vass, C; Schmetterer, L
Abstract : Background: There is evidence that perfusion abnormalities of the optic nerve head are involved in the pathogenesis of glaucoma. There is therefore considerable interest in the effects of topical antiglaucoma drugs on ocular blood flow. A study was undertaken to compare the ocular haemodynamic effects of dorzolamide and timolol in patients with primary open angle glaucoma (POAG) or ocular hypertension (OHT). Methods: One hundred and forty patients with POAG or OHT were included in a controlled, randomised, double blind study in two parallel groups; 70 were randomised to receive timolol and 70 to receive dorzolamide for a period of 6 months. Subjects whose intraocular pressure (IOP) did not respond to either of the two drugs were switched to the alternative treatment after 2 weeks. Scanning laser Doppler flowmetry was used to measure blood flow in the temporal neuroretinal rim and the cup of the optic nerve head. Pulsatile choroidal blood flow was assessed using laser interferometric measurement of fundus pulsation amplitude. Results: Five patients did not respond to timolol and were changed to the dorzolamide group, and 18 patients changed from dorzolamide treatment to timolol. The effects of both drugs on IOP and ocular perfusion pressure were comparable. Dorzolamide, but not timolol, increased blood flow in the temporal neuroretinal rim (8.5 (1.6)%, p<0.001 versus timolol) and the cup of the optic nerve head (13.5 (2.5)%, p<0.001 versus timolol), and fundus pulsation amplitude (8.9 (1.3)%, p<0.001 versus timolol). Conclusions: This study indicates augmented blood flow in the optic nerve head and choroid after 6 months of treatment with dorzolamide, but not with timolol. It remains to be established whether this effect can help to reduce visual field loss in patients with glaucoma.